A review of 50 years of research since Knickerbocker (1973): competitive dynamics in international business - Yao, Fiona Kun; Chen, Ming-Jer; Li, Jiatao; Combs, Danielle; Li, Qiang (Journal of International Business Studies, 2024)
Competition has long been considered a central element of strategy for multinational enterprises in classical foreign direct investment theories. This review evaluates the large and diverse literature on competitive dynamics in international business since Knickerbocker’s (Oligopolistic reaction and the multi-national enterprise, MIT Press, Cambridge, 1973) seminal work on oligopolistic reaction. Specifically, we review the literature on follow-the-leader, awareness–motivation–capability, competitor analysis, and multimarket competition. Our review reveals that competitive interaction in the international context is a multi-arena, multi-player, and multi-level phenomenon. We also identify opportunities for future research, such as deepening the understanding of the micro-foundations of competitive dynamics, incorporating more country-level factors into the analysis of firm-level competitive interactions, broadening the consideration of international stakeholders, and giving greater emphasis to non-market strategies as competitive actions in the global environment. Our review contributes to the development of international business theory by improving our understanding of the mechanisms underlying the execution and consequences of multinational firms’ competitive strategies. Moreover, it enriches the competitive dynamics theory in strategic management by emphasizing the complexities that the international context introduces to competitive interactions among firms.